Syria : U.S. Relations and Bilateral Issues. (U.S. Congressional Research., 2006)
Describes internal political scene of Syria, focusing on the Asad regime, its support groups, and Syrian opposition; and addresses domestic challenges. Reviews U.S.-Syria bilateral issues regarding Arab-Israeli peace negotiations, the role of Syria in Lebanon, relations with Iraq and Iran, arms proliferation, and terrorist activity; and surveys U.S. aid to and sanctions against Syria.